2002
DOI: 10.1017/s1068280500003464
|View full text |Cite
|
Sign up to set email alerts
|

An Hedonic Analysis of the Effects of Lake Water Clarity on New Hampshire Lakefront Properties

Abstract: Policy makers often face the problem of evaluating how water quality affects a region's economic well-being. Using water clarity as a measure of the degree of eutrophication levels (as a lake becomes inundated with nutrients, water clarity decreases markedly), analysis is performed on sales data collected over a six-year period. Our results indicate that water clarity has a significant effect on prices paid for residential properties. Effects of a one-meter change in clarity on property value are also estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 15 publications
2
95
0
Order By: Relevance
“…Consistent with previous investigations and for the ease of interpretation [3,14,30,33], water quality was proxied by Secchi depths collected during the summer months from 22 IDEQ monitoring stations throughout the lake. Milfoil data were obtained from a 2014 summary report published by Avista Corporation, which included a comprehensive survey of the occurrence of milfoil in Coeur d'Alene Lake from 2010 to 2014 [23].…”
Section: Datamentioning
confidence: 60%
See 1 more Smart Citation
“…Consistent with previous investigations and for the ease of interpretation [3,14,30,33], water quality was proxied by Secchi depths collected during the summer months from 22 IDEQ monitoring stations throughout the lake. Milfoil data were obtained from a 2014 summary report published by Avista Corporation, which included a comprehensive survey of the occurrence of milfoil in Coeur d'Alene Lake from 2010 to 2014 [23].…”
Section: Datamentioning
confidence: 60%
“…Secchi depth measurements were log transformed because people generally cannot perceive changes in water quality at deep compared to shallow depths [4,30]. To quantify the impacts of milfoil presence and ambient water quality on lakefront property values, separate hedonic models were estimated for the variables pertinent to the presence of milfoil and ambient water quality (Models 1 and 2 in Table 2), and then a combined regression model including both variables was run (Model 3 in Table 2).…”
Section: Model Specificationsmentioning
confidence: 99%
“…Numerous studies have found a relationship between the sale price of single-family residential properties and water quality (Gibbs et al, 2002;Laggett and Bockstael, 2000;Poor et al, 2007;Bin and Czajkowski, 2013). Water quality parameters that were most likely to be perceived by residents were selected for our analysis.…”
Section: Perception: Relationship Between Property Sale Prices and Wamentioning
confidence: 99%
“…For example, eutrophication in lakes has historically been identified as a cause for appraisal declines in residential property, especially in proximity to the degraded waterbody. In the northeastern USA, a 1.0 m decline in lake water clarity translated to a 1-6% decline in property value (Gibbs et al 2002). Conversely, improvements in water clarity can result in property price increases (Michael, Boyle, and Bouchard 1996).…”
Section: Introductionmentioning
confidence: 99%